Pengaruh Gaya Kepemimpinan Dan Quiet Quitting Terhadap Kinerja Karyawan Rumah Sakit Dan Klinik Pindad Bandung - Ridwan Juliansyah Resiana; Muji Rahayu (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine how leadership style and the phenomenon of quiet quitting contribute to employee performance levels. The subjects of this research consist of all non-medical staff working at the Pindad Clinic and Hospital in Bandung. This study was initiated due to a substantial gap identified in previous research, namely the absence of studies specifically examining quiet quitting among non-medical personnel in Indonesia’s healthcare sector, as well as the limited empirical evidence on how perceptions of leadership shape psychological withdrawal tendencies within this work environment. This study applied a descriptive quantitative method by distributing surveys to a total of 107 participants drawn from a population of 146 non-medical employees. The measurement of the instrument employed a Likert scale consisting of five response options, and statistical analysis was conducted using SPSS with linear regression to assess direct relationships among the variables. The results of Hypothesis 1 reveal that leadership style positively affects performance, but the effect does not reach statistical significance. Meanwhile, the analysis of Hypothesis 2 confirms that quiet quitting exerts a significant negative effect on performance, where decreased quiet quitting behavior is associated with enhanced employee performance.